2006
DOI: 10.1093/toxsci/kfl017
|View full text |Cite
|
Sign up to set email alerts
|

A Manganese-Enhanced Diet Alters Brain Metals and Transporters in the Developing Rat

Abstract: Manganese (Mn) neurotoxicity in adults can result in psychological and neurological disturbances similar to Parkinson's disease, including extrapyramidal motor system defects and altered behaviors. However, virtually nothing is known regarding excess Mn accumulation during central nervous system development. Developing rats were exposed to a diet high in Mn via maternal milk during lactation (PN4-21). The high Mn diet resulted in changes in hematological parameters similar to those seen with iron (Fe) deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 45 publications
8
62
0
1
Order By: Relevance
“…An in vivo study by Garcia et al showed that DMT1 expression increases by ∼35% in the brains of rat pups nurtured by dams fed with high Mn diet. This elevation in DMT1 expression is not region-specific; nonetheless, the data directly relate the effect of an enhanced Mn diet with augmentation in DMT1 expression (Garcia et al, 2006). In addition, this correlation is supported by in vitro data where exposure to Mn for 24 and 48 hours has been shown to increase DMT1 expression in the immortalized choroidal epithelial Z310 cell line by 45% and 78% respectively (Wang et al, 2006).…”
Section: Manganese and Dmt1mentioning
confidence: 57%
“…An in vivo study by Garcia et al showed that DMT1 expression increases by ∼35% in the brains of rat pups nurtured by dams fed with high Mn diet. This elevation in DMT1 expression is not region-specific; nonetheless, the data directly relate the effect of an enhanced Mn diet with augmentation in DMT1 expression (Garcia et al, 2006). In addition, this correlation is supported by in vitro data where exposure to Mn for 24 and 48 hours has been shown to increase DMT1 expression in the immortalized choroidal epithelial Z310 cell line by 45% and 78% respectively (Wang et al, 2006).…”
Section: Manganese and Dmt1mentioning
confidence: 57%
“…Mn exposure has been shown to affect tissue concentrations in a differential manner depending upon species and type of exposure. A significant increase in striatal GABA due to Mn exposure was found in rats (Garcia et al 2006(Garcia et al , 2007Gwiazda et al 2002); while a marginally significant (P < 0.1) decrease in pallidal GABA concentrations in monkeys exposed to airborne MnSO4 has been reported (Struve et al 2007); and no statistical difference was found in brain regional GABA concentrations in primates injected with Mn intravenously (Burton et al 2009). While tissue GABA concentrations can capture the overall status of GABA biology in an organism, it does not fully reflect the extracellular concentrations which are critical for neurotransmission.…”
Section: Effects Of Mn On γ-Aminobutyric Acidmentioning
confidence: 90%
“…Putative transport mechanisms in the adult include the divalent metal transporter 1 (DMT-1) and the transferrin receptor (TfR). Protein expression of DMT-1 and TfR is seen as early as postnatal day 5 (PN5) and increases through PN15 in all regions examined (cortex, hippocampus, striatum) (Siddappa et al, 2002;Garcia et al, 2006), verifying that DMT-1 and TfR are present in the developing brain; however, whether functional, remains unknown.…”
Section: Manganese Transport Into Brain Transferrin/transferrin Recepmentioning
confidence: 90%
“…To date it appears that the neonatal brain handles excessive Mn (via DMT-1 upregulation and to a lesser extent Tf/TfR) similarly to the adult brain (Garcia et al, 2006). In terms of neurochemical alterations associated with Mn-exposure in early life, both dopamine (Tran et al, 2002) and GABA (Garcia et al, 2006) have been implicated.…”
Section: Direction For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation